2011
DOI: 10.5754/hge10501
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Nrf2 Expression in Non-Alcoholic Fatty Liver and Steatohepatitis

Abstract: Our results showed that during the development of NAFL and NASH, F2-isoPG levels increased and Nrf2 expression was upregulated. Our findings suggest Nrf2 may play a key role during liver steatosis, and activation of Nrf2 may protect liver from inflammation damage induced by oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…Many researches have demonstrated that Nrf2 prevents the liver from many hepatotoxicants. The Nrf2-mediated protection is accompanied by induction of antioxidant genes, suppression of inflammatory responses, inhibition of apoptosis and attenuation of oxidative stress [7,8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researches have demonstrated that Nrf2 prevents the liver from many hepatotoxicants. The Nrf2-mediated protection is accompanied by induction of antioxidant genes, suppression of inflammatory responses, inhibition of apoptosis and attenuation of oxidative stress [7,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor E2-related factor 2 (Nrf2) is referred to as the ''master regulator'' of the antioxidant response via the antioxidant response elements (ARE), modulating the expression of hundreds of genes, including not only the familiar antioxidant enzymes, but large numbers of genes that control seemingly disparate processes such as immune and inflammatory responses, tissue remodelling and fibrosis, carcinogenesis and metastasis, and even cognitive dysfunction and addictive behavior [7][8][9]. Many researches have demonstrated that Nrf2 prevents the liver from many hepatotoxicants.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor erythroid-2-related factor 2 (Nrf2) is known as the “primary supervisor” of the antioxidant response through the antioxidant response elements (AREs), regulating the expression of numerous genes including heme oxygenase-1 (HO-1), NAD(P)H quinone oxidoreductase 1 (NQO1), and glutathione S -transferase (GST) and several adenosine triphosphate-dependent drug efflux pumps (multidrug resistance proteins) 35. Therefore, many studies have demonstrated that Nrf2 is a transcription factor that can regulate various cytoprotective genes.…”
Section: Introductionmentioning
confidence: 99%
“…Free Nrf2, dissociated from keap1, moves into the nucleus, combines with ARE, and serves as a transcriptional factor to regulate the expression of corresponding downstream genes ( e.g ., GSH and HO-1 ). This comes with enhanced oxidation resistance and reduced oxidative stress[6,7,26]. So, the means by which to increase the expression of Nrf2 or promote Nrf2 nuclear translocation could be an important target for the treatment and prevention of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%